STANDARADIZATION OF MEAT ANALOGUES INCORPORATED WITH TENDER JACKFRUIT - H. J .K. NOVA* (The Journal of Research ANGRAU, 2023)
The study was carried out for three months during 2021 at Department of Community Science, College of Agriculture, Kerala Agricultural University, Vellanikkara and standardization was done formulating varied treatments of meat analogues followed by organoleptic evaluation in which sensory attributes such as appearance, colour, flavour, taste, texture and overall acceptability of tender jackfruit incorporated cowpea and chickpea meat analogues were evaluated. The results revealed that among different treatments, the treatments T5 (40% CWP+25% TJ +25% WG +5% DSF +5% OMF) and T10 (50% CP+20% TJ+20% WG +5% DSF +5% OMF) were observed to have highest scores for all the sensory attributes including appearance, colour, flavour, texture, taste and overall acceptability of tender jackfruit incorporated meat analogues, respectively. Statistical analysis by applying Kendall’s (W) test showed that Kendall’s (W) value among different treatments of each set of both tender jackfruit incorporated meat analogues was highly significant with regards to all quality attributes. This study revealed that incorporation of wheat gluten along with tender jackfruit both at 20-25 percent showed improved sensory qualities such as texture, flavour, taste and overall acceptability with higher consumer preference.